African Print Cultures : Newspapers and Their Publics in the Twentieth Century - Newell, Stephanie, 1968-; Hunter, Emma, 1980-; Peterson, Derek R., 1971- (Book collections on Project MUSE., 2016)
This inaugural volume in the African Perspectives series features the workof new and well-established scholars on the diversity and heterogeneityof African newspapers published from 1880 through the present. Newspapers played a critical role in spreading political awareness amongreaders who were subject to European colonial rule, often engaging inanticolonial and nationalist discourse or popularizing support for Africannationalism and Pan-Africanism. Newspapers also served as incubatorsof literary experimentation and new and varied cultural communities. The contributors highlight the actual practices of newspaper productionat different regional sites and historical junctures, while also developinga set of methodologies and theories of wider relevance to socialhistorians and literary scholars. The first of four thematic sections, "African Newspaper Networks," considers the work of newspapereditors and contributors in relating local events and concerns to issuesaffecting others across the continent and beyond